Pengaruh Kecerdasan Emosional Dan Kecerdasan Spiritual Terhadap Kinerja Pegawai Di Rsjko Soeprapto Bengkulu Dimediasi Oleh Motivasi Kerja - Adian Saputra; Fahrudin Js Pareke; I Wayan Dharmayana (Student Journal of Business and Management, 2023)
This study aims to analyze the effect of emotional intelligence, spiritual intelligence on work motivation and nurse performance. In addition, the study also analyzed the mediating role of work motivation on the influence of emotional intelligence and spiritual intelligence on performance. This research is a type of descriptive research with a quantitative approach (survey). The type of data used is primary data obtained through distributing questionnaires. Respondents of this study were 49 nurses of RSJKO Soeprapto Bengkulu. The data analyzed used descriptive analysis and PLS analysis with the help of the SmartPLS version 3 application. Based on field research, the results obtained that (1) The effect of emotional intelligence on work motivation is not significant. This means that changes in emotional intelligence have no impact on nurses' work motivation; (2) The effect of spiritual intelligence on work motivation is significantly positive. This means that the higher the spiritual intelligence of nurses, the impact on nurses' work motivation; (3) Work motivation has a positive effect on performance. This means that the higher the nurse's work motivation, the higher the nurse's performance; (4) Work motivation does not mediate the effect of emotional intelligence on performance. This means that work motivation does not play a role in the effect of emotional intelligence on performance; and (5) Work motivation mediates the effect of spiritual intelligence on performance. This means that work motivation plays a role in the influence of spiritual intelligence on performance. The mediation role is partially mediation.